Perspectives on Arabic Linguistics : Papers from the Annual Symposium on Arabic Linguistics. Volume IV: Detroit, Michigan 1990. - Broselow, Ellen (John Benjamins Pub. Co., 1992)
This volume includes papers on the study of Arabic dialects and their implications for general linguistics (Section I), as well of papers of a more general nature (Sections II and III). Because the Arabic dialects are similar in many ways, a study of their differences can help isolate precisely the range of permissible interlinguistic variation (i.e. the "parameters" of universal grammar). A number of papers in Section I focus on the contribution of dialect studies to a theory of crossdialectal and crosslinguistic variation; others focus on individual dialects, thus providing data and analyses.